Os Kaingang de Cacique Doble e a política indigenista do Serviço de Proteção aos Índios : trabalho, educação e integração (1941-1967) - Vanin, Alex Antônio (2020)
The present study aims to contemplate, as main theme, the indigenous policy of the Indian Protection Service (SPI), during the period from 1941 to 1967, in a specific experience of its implementation among the Kaingang of the Cacique Doble Indigenous Post, this located in the north / northeast region of the state of Rio Grande do Sul. The research problem is centered on understand the consequences of this policy, around the changes resulting from it’s implementation among the Kaingang of Cacique Doble, in the areas of social relations, work, production and relationship with the land and the conflicts that made up this reality. The sources used are mainly composed of the SPI documentation referring to the Cacique Doble Indigenous Post, bibliographic sources about the region where it was inserted and also institutional documents from the federal agency and the ministries to which it was subordinated. It is intended to understand the aspects of structure the indigenous integration project, in this period when the objectives of indigenous action are reoriented and acquire features corresponding to the changes that occur in the development of national economic production, with the adoption of developmentalism as a model of economic growth. The SPI becomes the driver of this new economic orientation, which materialized in indigenous action through the objective of training productive rural workers. Around this, the SPI action aimed to fix the Kaingang to the land, delimit its territoriality to the space defined by the federal agency, with a view to elevating it to the intended condition of rural worker, capable of achieving its emancipation from state tutelage. At the same time, it was attempted to integrate the indigenous people through the introduction of an educational system that aimed at the nationalization of the Kaingang, the overlapping of their vernacular language, customs and inserted rituals aimed at the cult of the nation. Therefore, the SPI at the Cacique Doble Indigenous Post, sought to redefine the indigenous social and spatial organization, through work and education, instituting for both a strict discipline based on a regime of punishments, which, however, before being passively accepted by Kaingang, faced indigenous resistance to these integrative processes.